The inverse is not a function because it fails the vertical line test.
To find the inverse of a function, you replace x with y and y with x. Here, y=2x-4 would become x=2y-4. Now, we solve for y. 2y=x+4. y=(x/2)+4, and that is the inverse equation.
Simply stated, the inverse of a function is a function where the variables are reversed. If you have a function f(x) = y, the inverse is denoted as f-1(y) = x. Examples: y=x+3 Inverse is x=y+3, or y=x-3 y=2x+5 Inverse is x=2y+5, or y=(x-5)/2
Put simply, the inverse of y=x^5+x^4+x is x=y^5+y^4+y. Unfortunately, this is a quintic function and there is no quintic formula.
No. A simple example of this is y = x2; the inverse is x = y2, which is not a function.
if f(x) = 4x, then the inverse function g(x) = x/4
In order for a fourth degree function to have an inverse function, its domain must be restricted. Otherwise the inverse function will not pass the vertical-line test.Ex.f(x) = x^4 (x>0), the original functionf-1(x) = x ^ (1/4), the inverse
A reciprocal function will flip the original function (reciprocal of 3/5 is 5/3). An inverse function will change the x's and y's of the original function (the inverse of x<4,y>8 is y<4, x>8). Whenever a function is reflected over the line y=x, the result is the inverse of that function. The y=x line starts at the origin (0,0) and has a positive slope of one. All an inverse does is flip the domain and range.
1
The inverse is not a function because it fails the vertical line test.
The inverse for f(x) = 4x + 8 isg(x) = x/4 - 2
To find the inverse of a function, you replace x with y and y with x. Here, y=2x-4 would become x=2y-4. Now, we solve for y. 2y=x+4. y=(x/2)+4, and that is the inverse equation.
X squared is not an inverse function; it is a quadratic function.
The inverse for f(x) = 4x + 8 isg(x) = x/4 - 2
Because the inverse of a function is what happens when you replace x with y and y with x.
The inverse of the function y = x is denoted as y = x. The inverse function essentially swaps the roles of x and y, so the inverse of y = x is x = y. In other words, the inverse function of y = x is the function x = y.
If the quadratic function is f(x) = ax^2 + bx + c then its inverse isf'(x) = [-b + +/- sqrt{b^2 - 4*(c - x)}]/(2a)